Neutron Radiographic Imaging Analysis - Butler, Michael Paul (My University, 1980)
In analyzing the processes involved in neutron radiography, there is a need for a well-defined mathematical structure which can simultaneously be used in practical situations without great difficulty. In this report, the edge-spread function method of analysis is considered in some detail. The basic theory is developed, and both the general and the specific viewpoint are considered, in terms of the mathematical functions used. The usefulness of ESF theory in predicting optical density patterns is illustrated. Specific applications of the theory are developed; in particular, studies of image resolution and unsharpness are undertaken.
To determine whether or not ESF methods are a good representation of the physical situation, some alternate methods which consider radiography from a more basic viewpoint are developed. The first of these is a strictly numerical approach, where experimental data is examined without specifying a model for the image formation process; a matrix formulation suitable for characterizing an image is developed.
The second alternate method involves the use of Monte Carlo methods; this allows the incorporation of more realistic parameters into the analysis. For example, screen-film separation and object scattering of neutrons, and their effects on the image, are evaluated. Finally, a two-dimensional analysis of a simple problem is considered, with the end result being a confirmation of the usefulness of ESF theory.
Keywords: radiography, neutron radiography, edge-spread function method, ESF theory, ESF, numerical approach, Monte Carlo methods, Monte Carlo